Delayed persistence of giant-nucleated cells induced by X-ray and proton irradiation in the progeny of replicating normal human f ibroblast cells. (August 2017) - Almahwasi, A.A.; Jeynes, J.C.; Merchant, M.J.; Bradley, D.A.; Regan, P.H.
Abstract: Ionising radiation can induce giant-nucleated cells (GCs) in the progeny of irradiated populations, as demonstrated in various cellular systems. Most in vitro studies have utilised quiescent cancerous or normal cell lines but it is not clear whether radiation-induced GCs persist in the progeny of normal replicated cells. In the current work we show persistent induction of GCs in the progeny of normal human-diploid skin fibroblasts (AG1522). These cells were originally irradiated with a single equivalent clinical dose of 0.2, 1 or 2 Gy of either X-ray or proton irradiation and maintained in an active state for various post-irradiation incubation interval times before they were replated for GC analysis. The results demonstrate that the formation of GCs in the progeny of X-ray or proton irradiated cells was increased in a dose-dependent manner when measured 7 days after irradiation and this finding is in agreement with that reported for the AG1522 cells using other radiation qualities. For the 1 Gy X-ray doses it was found that the GC yield increased continually with time up to 21 days post-irradiation. These results can act as benchmark data for such work and may have important implications for studies aimed at evaluating the efficacy of radiation therapy and in determining the risk of delayed effects particularly when applying protons. Highlights: Study of giant-nucleated cell development post X-ray and proton irradiation. A vertical beamline used to irradiate AG1522 cells with protons in vitro. Measurement of cross-sectional area of AG1522 nuclei. X-irradiation observed to induce giant-nucleated cells in a dose-dependent manner. A cell-recognition MATLAB code used to identify giant-nucleated cells.